SALAH URUS TERHADAP PERUSAHAAN MULTINASIONAL SHELL DAN DAMPAKNYA BAGI PEREKONOMIAN NIGERIA TAHUN 2010-2012 - Leidy Glameidya (HI 15 UMY 400, 2015)
*400 Oil is the one of energy resources that the most widely used than the other energy resouces. The long history of colonialism in Nigeria has made this country discovered the potential of natural resources with found some oil sources. Geographical location and the dynamics of economic and political support for the management of the oil in this country so that Nigeria became an example of a country that relies on oil revenue. Management of oil in Nigeria can not be separated from the role of Multinational Corporations that Shell has found oil resources and also did the first mining activities in Nigeria. The achievement of high oil production generated Shell made the government formed a partnership with Shell. Nigeria managed to be recognized as a country with rapid economic growth in Africa and in the world. Unfortunately, the degree of people's lives are not as high as that achieved overall GDP. Abundant oil production as a result of processing by Shell can not support the economy of the people of Nigeria. Thus, the concept of Multinational Corporations and the concept of Weak State relevant to analyze this problem. So it will support the reason for this study is to prove insignificant existence Shell with the Nigerian economy. Keywords: Nigeria, Shell, Nigerian Government, Economy of Nigeria